The Role of Career Women in Creating a Sakinah Family: From Mubadalah (Mutuality) Perspective - Nastangin, Nastangin; Huda, Muhammad Chairul (al-'adalah, 2022)
Abstract: The Role of Career Women In Creating A Sakīnah Family: From Mubādalah (Mutuality) Perspective. Career women have dual roles, first as a wife and second as a worker. This dual role, either directly or indirectly, will affect their ability to manage domestic life. This study tries to examine this phenomenon through the perspective of mubādalah (mutuality) from Faqihuddin Abdul Kodir. The aim is to find out the success/failure of how career women reconcile their roles as housewives as well as career women. This research is qualitative by using a socio-legal approach. Data were collected using in-depth interview techniques conducted with several female lecturers at IAIN Salatiga. This study finds the fact that the perspective of Mubādalah (Mutuality) theory, when drawn into the realm of family life of female lecturers at IAIN Salatiga, is in line because Mubādalah theory requires a balance of relations between husband and wife and the elimination of gender bias to create a harmonious and prosperous family life.